Influence of hexylamine on kinetics of flotation and bubble attachment to the quartz surface. Issue 15 (1st November 2016) - Kowalczuk, Przemyslaw B.; Zawala, Jan; Drzymala, Jan; Malysa, Kazimierz
ABSTRACT: In this work flotation and single bubble tests were conducted with high purity quartz in water and hexylamine solutions at different pHs. It was found that flotation kinetics and time of the three-phase contact (TPC) formation ( t TPC ) at the quartz surface by the colliding bubble were affected by the hexylamine concentration and the solution pH. The TPC of the quartz/air bubble/hexylamine system was formed within the pH range 4–12. A strong relationship between the t TPC and flotation kinetics expressed as an inverse of the first-order rate constant (1/ k ) was obtained. The t TPC and 1/ k values were the shortest within similar pH range.